TEKNOLOGI ERA GLOBALISASI ANTARA HARAPAN DAN TANTANGAN - usman usman (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2007)
Television or Google-Box is one of the mass media becoming furniture which atmost occupying collective imagination room of society. Realized or not, telecasteffectively alter not even public opinion about something, however also alter someone life style or society. Display hardness becoming the part of pre eminent broadcast a mumber of television station have been long enough been felt concerned about by many people, especially the parent. Their assume, display  hardness on television can push someone (their child) becoming less sensitive to hardness that happened around them. Even, non improbability, the hardness they will practice in life of reality to friend play just or conducive to whom earn them do. Its death a child fin) Katapang can become strong sample to the truth of the ascription At least the "Smack Down" have deputized various event presenting was displayed in television